Anxiety, nause and vomiting management in controllingblood pressure patients post general anesthesia surgery - Budi Antoro; Yuli Lestari; Nova Nurwinda Sari; Tubagus Erwin (Universitas Aisyah Pringsewu, 2023)
Surgery is a follow-up action for emergency treatment which often causes physiological reactions for the patient and requires hemodynamic monitoring such as blood pressure to prevent delays in action and complications. Excessive anxiety can change blood pressure so that it has an impact on delaying surgery schedules. Meanwhile, post-surgery nausea and vomiting are the symptoms that most often arise as a result of anesthesia. This study aims to determine the relationship between anxiety management, nausea and vomiting in controlling blood pressure in patients after general anesthesia surgery at Pringsewu Hospital, Lampung Province. This type of research is quantitative, with a research design and analytic survey design with a cross-sectional approach. The population was all preoperative soft tissue tumor patients under general anesthesia at Pringsewu Hospital, Lampung Province with a total sample of 38 respondents. The results of the study showed that there was a relationship between the level of anxiety and an increase in preoperative general anesthesia blood pressure at the Pringsewu General Hospital in Lampung Province with a p-value of 0.000 (p-value less than 0.05); There was no relationship between nausea and vomiting responses with postoperative blood pressure in Pringsewu Hospital, Lampung Province with a p-value of 0.574 (p-value more than 0.05). Post-surgical patient care needs to get proper care according to pre- and post-operative procedures for surgical patients in order to minimize the occurrence of various effects of the anesthesia obtained.